ANALISIS MODAL PINJAMAN DAN RENTABILITAS EKONOMI PADA KOPERASI PEGAWAI REPUBLIK INDONESIA (KPRI) KARYA BHAKTI DINAS KOPERASI UMKM PERINDUSTRIAN DAN PERDAGANGAN PROVINSI SULAWESI TENGAH - HASLAN, KHARISMAN (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2015)
This research aims to determine, understand, and analyze the influence of capital lending and economic profitability on the cooperative for The Indonesian Republic officials ?Karya Bhakti? of The Departement of Industry Cooperation and Trading at Central Sulawesi Province. It is a descriptive research using quantitative and qualitative approach that consists of primary data and secondary data. Data collection method to obtain the primary data is observation on Karya Bhakti Employee Cooperative as the subject of research and secondary data obtained from the financial annual report Karya Bhakti Cooperative. The analysis of loan capital and economic profitability of Karya Bhakti Cooperative is measured by using trend analysis. Based on the data analysis from 2008 to 2013, it indicates that the development of Loan capital has increased every year. This is due to the development of the business managed by the cooperatives operations, while the development of the economic profitability has been fluctuated, as well as the result of trend analysis of capital lending and economic profitability showed an increase every year.